Long-run Relationship Between Government Debt and Growth: the Case of Indonesia - Handra, Hefrizal; Kurniawan, Budi (International Journal of Economics and Financial Issues, 2019)
This study examines long-run relationship between the government debt and economic growth in Indonesia. This study uses the Autoregressive Distributed Lag (ARDL) cointegration method. Employing a time series data from 1980 to 2017, this study reveals that there is a negative long-run relationship between the ratio of government debt to GDP and the economic growth. That means the growth of debt ratio to the GDP could lower the growth in a long term. Keywords: Economic Growth; Government Debt; Indonesia. JEL Classifications: C22, H63 DOI: https://doi.org/10.32479/ijefi.8956